Association Between Suicidal Attempts in Connection to Discrimination Among Trans Genders: suicidal attempts in connection to discrimination among trans genders - Ali, Asghar; Ahmed Khan, Saad; Zeb, Shah; Munir, Zahir; Saeed Ali, Tazeen (Pakistan Journal of Health Sciences, 2022)
Suicide has become a serious public health challenge across the world with around 800,000 people dying by suicide each year. Amongst these a majority of the people (79%) belongs to low and middle-income countries. Objective: The study aimed to identify the association between suicidal attempts in connection to discrimination among transgender. Methods: An analytical cross-sectional study was conducted. Data were collected from a registered NGO (Gender Interactive Alliance) from February to May, 2020, using a universal and purposive sampling technique. Data was analyzed on SPSS (version 21.0). Mean and standard deviation was calculated for frequency distribution, while Chi-square was used for categorical variables. Results: Overall, 250 transgender were approached through a registered NGO. The mean age of participants was 32.34 years with a standard deviation of 7.86 years. From this, 88.4% were males and 11.6% were females as identified by their birth certificates. The current sex/gender the participants identified as 81.6% Males and 18.4% Females. Half of the participants were homeless while 33.6% were living in a shelter. The suicidal attempt was identified in 62.9% of Males, 13.5% of Females, and 23.6% of trans genders, as identified by their N.I. Cs (p-value X2 0.012). Based on monthly income, 36% of the participants who made monthly income between 21000 to 30000 PKR, reported suicidal attempts with a significant p-value of X2 0.034. Conclusions: This study found an association between discrimination and suicidal attempt among a transgender population